2017
DOI: 10.22489/cinc.2017.245-303
|View full text |Cite
|
Sign up to set email alerts
|

ECG Imaging of Simulated Atrial Fibrillation: Imposing Epi-Endocardial Similarity Facilitates the Reconstruction of Transmembrane Voltages

Abstract: Electrocardiographic imaging (ECGI) could help in diagnosis and treatment of atrial fibrillation (AF), the most common life-threatening arrhythmia. Based on a previous work by Figuera et al. on the reconstruction of epicardial potentials (EP) during AF, we explore the performance of a Tikhonov regularization with two spatial constraints for transmembrane voltage (TMV) based ECGI. We develop a new method to impose epi-endocardial similarity and show its benefit for ECGI of atrial activity. Apart from TMVs, loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Figure 2 shows the geometries used for forward and inverse calculations. They are the same as in Schuler et al ( 2017 ), which in turn are based on Figuera et al ( 2016 ). The surface meshes of the atria and torso consist of 4,800 and 844 nodes and have an average edge length of 3.4 and 27.0 mm, respectively.…”
Section: Methodsmentioning
confidence: 90%
“…Figure 2 shows the geometries used for forward and inverse calculations. They are the same as in Schuler et al ( 2017 ), which in turn are based on Figuera et al ( 2016 ). The surface meshes of the atria and torso consist of 4,800 and 844 nodes and have an average edge length of 3.4 and 27.0 mm, respectively.…”
Section: Methodsmentioning
confidence: 90%
“…As Tikhonov regularization is applied to all time steps simultaneously, the regularization parameters λ and η are constant over time. For fibrillatory activity, it was found that constant parameters do not impair the solution quality compared to instantaneous ones [2]. In this work, the optimal Tikhonov parameters were obtained by maximizing the temporal mean of spatial TMV correlation with the ground truth using downhill simplex optimization.…”
Section: Tikhonov Regularizationmentioning
confidence: 99%
“…A more realistic geometry of the torso and the atria is later used to demonstrate the new regularization method in an application to irregular atrial activity. The geometry is the same as in [2], but the number of atrial nodes has been reduced to 1696 in order to speed up computations. The "simple atrial fibrillation" simulation from [3] is chosen as activity to be reconstructed, which includes rotational activity on the right atrium repeating at 7.3 Hz, while the left atrium is activated at 4.7 Hz.…”
Section: Geometries and Excitation Patternsmentioning
confidence: 99%
See 2 more Smart Citations